2021
DOI: 10.3389/fenrg.2021.735551
|View full text |Cite|
|
Sign up to set email alerts
|

Energy Efficiency and Pollution Control Through ICTs for Sustainable Development

Abstract: The goal of this paper is to prove the necessity for a more thorough consideration and more active use of the modern ICTs for the technological support for the practical implementation of the SDGs’ ecological block in the aspect of the increase of energy efficiency and environmental pollution control. The originality of this paper is as follows: it develops a proprietary methodology of evaluating the technical readiness (level of the development of ICTs) for implementing the ecological block of the SDGs, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Wang et al [35] constructed an ICT maturity index to study the impact of China's ICT development on energy consumption in different stages during the period 2001-2030, and concluded that although the development of ICT could slow down the continuous growth of energy consumption by improving energy efficiency, the use of ICT increased energy consumption; this was in line with the findings of Lange et al [36]. Popkova et al [37] concluded that the use of ICT in e-government could improve energy efficiency and reduce environmental pollution, and that there were differences in the effects between developed and developing countries. Bildirici et al [38] studied the G7 countries during the period 1990-2020 and showed that in the short term, the development of ICT increased energy consumption and environmental pollution, but in the long term, it improved energy efficiency, promoted economic growth, and reduced environmental pollution.…”
Section: Ict and Energy Efficiencymentioning
confidence: 54%
“…Wang et al [35] constructed an ICT maturity index to study the impact of China's ICT development on energy consumption in different stages during the period 2001-2030, and concluded that although the development of ICT could slow down the continuous growth of energy consumption by improving energy efficiency, the use of ICT increased energy consumption; this was in line with the findings of Lange et al [36]. Popkova et al [37] concluded that the use of ICT in e-government could improve energy efficiency and reduce environmental pollution, and that there were differences in the effects between developed and developing countries. Bildirici et al [38] studied the G7 countries during the period 1990-2020 and showed that in the short term, the development of ICT increased energy consumption and environmental pollution, but in the long term, it improved energy efficiency, promoted economic growth, and reduced environmental pollution.…”
Section: Ict and Energy Efficiencymentioning
confidence: 54%
“…Integrating smart grid technologies is crucial for addressing the challenges posed by expanding renewable energy sources. Smart grids offer numerous advantages, such as energy efficiency, greenhouse gas reduction, and cost-effective administration of the power supply (Kabeyi & Olanrewaju, 2022;Moreno Escobar et al, 2021;Moretti et al, 2017;Popkova et al, 2023). In load forecasting, energy consumption modeling, and DSA, applying ML algorithms has yielded encouraging results.…”
Section: Smart Gridmentioning
confidence: 99%
“…Untuk mencapai kelestarian lingkungan, kebijakan TIK perlu lebih ditekankan untuk memitigasi masalah lingkungan di negara-negara kurang berkembang. Hal ini seperti studi (Popkova, Inshakova, Bogoviz, & Lobova, 2021) membuktikan perlunya pertimbangan yang lebih menyeluruh dan penggunaan TIK modern yang lebih aktif untuk dukungan teknologi untuk implementasi praktis dari blok ekologis SDGs dalam aspek peningkatan efisiensi energi dan pengendalian pencemaran lingkungan. Hal ini menegaskan bahwa potensi besar TIK dalam stimulasi pertumbuhan efisiensi energi dan pengurangan pencemaran lingkungan di negara maju dan berkembang.…”
Section: Hasil Dan Pembahasanunclassified